(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the weight change and ghrelin, obestatin and leptin levels in operated early stage breast cancer patients receiving adjuvant chemotherapy. Material and Methods: This study was conducted with 22 operated breast cancer patients (examined before and after adjuvant chemotherapy) and 33 BMI-matched two different healthy controls (of 33 healthy controls, 17 BMI-matched control was used to compare before adjuvant chemotherapy, 16 BMI-matched control was used to compare after adjuvant chemotherapy). Age, anthropometric measurements (weight, BMI, waist circumference), and blood biochemistry were recorded. Blood and salivary total ghrelin, obestatin and leptin levels are measured by using ELISA.Results: The mean ± SD weight (67.2 ± 12.3 and 72.9 ± 11.8 kg., p0.001), BMI (27.3 ± 4.7 and 29.61 ± 4.4 kg/m2, p0.001) and waist circumference (88.6 ± 10.8 and after adjuvant chemotherapy, (93.4 ± 11.0 cm., p0.05) values increased significantly when compared to pre-treatment values. Acyl ghrelin (74.05 ± 50.85 and 186.47 ± 89.61 pg/ml., p0.001 and 59.28 ± 45.74 and 151.74 ± 94.88 pg/ml., p0.01) and des-acyl ghrelin (347.59 ± 241.95 and 936.76 ± 446.93 pg/ml., p0.001 and 295.40 ± 241.44 and 765.38 ± 471.74 pg/ml., p0.01) serum levels were significantly lower in breast cancer patients compared to the control group in both pre-treatment and post-treatment periods.Conclusion: In conclusion, our study confirms that adjuvant chemotherapy causes significant weight gain in early stage breast cancer patients but does not indicate a concomitant treatment related change in ghrelin, leptin or obestatin levels. The fact that serum ghrelin levels were lower in breast cancer patients compared to BMI-matched control group, independent from treatment, might indicate that ghrelin-specific weight or adjuvant chemotherapy may be a regulatory mechanism for cancer etiopathology in breast cancer patients.